Mineral Composition and the Provenance of the Sediments of Thar Coal Basin - Abdallah, R. M.; Baig, M. A. A.; Abro, A.R.; Saghir, Ahmad; Pathan , M. A.; Ahmed, M.R. (Journal of Himalayan Earth Sciences, 1997)
Ten core samples of two bore-holes from the Tharparker coal basin were investigated for their mineral composition, depositional environments, origin of the mineral phases and the provenance of the studied sediments. X-ray diffraction of the whole-rock and the clay fraction (<2g) indicated that the samples are composed of detrital components dominated by quart: and Total clays. However, feldspar, biotite and siderite, have shown their presence by very weak XRD peaks in restricted samples. The X-ray diffraction of the clay fraction indicated that well crystalline kaolinite is present in samples of both the boreholes. Appreciable amount of illite and Mixed-layer clays are present in STP-13 samples, whereas, chlorite has shown its presence only in one sample of STP-13. All the samples of STP-1 borehole indicated the presence of appreciable amount of chlorite and negligible amount of mixed-layer clays. The clay mineral species appear to be detrital in origin, they might have been produced by the weathering of the source rock, having abundant amounts of minerals e.g. quartz, feldspar and Mg-rich silicates. The presence of well crystalline kaolinite and chlorite in STP-11 borehole samples suggest that the provenance of these sediments was in igneous/metamorphic rocks. The abundance of illite and Mixed-layer clays in STP-13 sediments, strongly suggest contribution of meta-sediments from the source area, a separate provenance, located most probably to the east of the site of this borehole. The dominant abundance of the detrital components i.e. quartz, kaolinite and total clays, suggest a near-shore deposition of these sediments, under reducing conditions which is indicated by the presence of mineral siderite and the deposits of coal.